Ineffective integration of multiple anti-predator defenses in a rotifer: a low-cost insurance?. (1st December 2022) - He, Yuhan; Zhu, Konghao; Zhao, Kangshun; He, Liang; Candolin, Ulrika; Xu, Jun; Zhang, Huan
Abstract: To maximize survival, prey often integrates multiple anti-predator defenses. How the defenses interact to reduce predation risk is, however, poorly known. We used the rotifer Brachionus calyciflorus to investigate how morphological (spines) and behavioral (floating) defenses are integrated against a common predatory rotifer, Asplanchna brightwellii, and if their combined use improves survival. To this end, we assessed the cost of the behavioral defense and the efficiency of both defenses, individually and combined, as well as their mutual dependency. The results show that the behavioral defense is costly in reducing foraging activity, and that the two defenses are used simultaneously, with the presence of the morphological defense enhancing the use of the behavioral defense, as does the pre-exposure to predator cues. However, while the morphological defense reduces predation risk, the behavioral defense does not, thus, adding the costly behavioral defense to the morphological defense does not improve survival. It is likely that the cost of the behavioral defense is low given its reversibility—compared to the cost of misidentifying the predator species—and that this has promoted the adoption of both defenses, as general low-cost insurance rather than as a tailored strategy toward specific predators. Thus, the optimal strategy in the rotifer appears to be to express both morphological and behavioral defenses when confronted with the cues of a potential predator. Abstract : When predators are around, no effort should be spared in defending oneself. We show that the rotifer, Brachionus calyciflorus, uses both spines on its body and floating behavior to defend itself when exposed to predator cues. However, only spines are needed to reduce predation risk. It seems likely that the low cost of floating has promoted its adoption, in addition to the possession of spines: it offers a general low-cost insurance against predation.